The Use of Irene's Donuts Media to improve Maternal Knowledge and Dental Health Status of Children in State Kindergarten 1 Pembina Bukit Lama Urban Village, Ilir Barat I District, Palembang City - Yufen Widodo; Meyrisa Bastari; Dhandi Wijaya (UrbanGreen Central Media, 2022)
This community service activity is to improve the knowledge and dental health status of children at State Kindergarten 1 Pembina Palembang City, with the use of irene's donuts media, in an effort to support the Indonesia caries-free action program in 2030. Efforts made so far have not obtained optimal results, so it is necessary to make efforts to prevent caries early through the Innovative UKGS program in which there is the use of irene's donut media. The community service carried out is a Community Partnership Program. The target was to increase the knowledge and oral health status of children at State Kindergarten 1 Pembina Palembang City. The results of this activity are increased maternal knowledge, children's dental health status and can detect caries early. They participated in this activity from the initial stage to the assistance, they really felt the positive impact of this community service activity, so that their oral health status became better than before.